EXISTENTIAL THEMES: SOCIAL WORKERS' PERSPECTIVES ON DEVELOPING THERAPEUTIC PRESENCE THROUGH SUPERVISION - Ioana-Eva CĂDARIU (International Journal of Social and Educational Innovation)
This qualitative study explored how social workers undergoing supervision in integrative psychotherapy develop therapeutic presence in the face of difficult existential themes and identify directions perceived as relevant for future practice. Twenty social workers completed an online questionnaire via Google Forms. Demographic data were analyzed with IBM SPSS Statistics for macOS, version 30.0 (IBM Corp., 2024), and qualitative responses were processed through thematic analysis (Clarke & Braun, 2017). The resulting themes focused on developing authentic presence, working with trauma and attachment, supporting adolescents, and integrating existential and spiritual dimensions into practice. The results emphasize the importance of ongoing training and personal development for strengthening therapeutic competence.